2008
DOI: 10.1007/s10562-008-9481-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of P Content on the Catalytic Performance of P-modified HZSM-5 Catalysts in Dehydration of Ethanol to Ethylene

Abstract: A series of phosphorus (P) modified HZSM-5 catalysts were prepared and characterized with various techniques. These catalysts were used in dehydration of ethanol to ethylene at different temperatures. It was found that not all the P-modified catalysts favor this reaction at high temperatures. Over the catalyst with 3.4 wt% P, the main product is ethylene at 573-713 K, due to the presence of weak acid sites after P modification. When the P loading is below 3.4 wt%, ethylene and higher hydrocarbons are observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 28 publications
1
65
0
Order By: Relevance
“…In a number of researches, they were observed that the acidity over solid catalysts predominantly plays an important role on alcoholic dehydration. The presence of strong acid sites on alumina catalysts increases the alcoholic conversion 14,23,24 . The result indicated that the dehydration activity was independent of the amount of acid sites on the catalyst.…”
Section: Ethanol Dehydration Reactionmentioning
confidence: 99%
“…In a number of researches, they were observed that the acidity over solid catalysts predominantly plays an important role on alcoholic dehydration. The presence of strong acid sites on alumina catalysts increases the alcoholic conversion 14,23,24 . The result indicated that the dehydration activity was independent of the amount of acid sites on the catalyst.…”
Section: Ethanol Dehydration Reactionmentioning
confidence: 99%
“…Actually, SAPO catalysts are significantly active in this reaction, reaching 98.0% selectivity to ethylene, at 250 °C, over SAPO 11 4 and 98.4%, at 340 °C, over Mn SAPO 34 [35,36]. However, over modified HZSM 5 and MCM 41 catalysts, selectivity to C2H4 is even higher (i.e., 99.0%) [37]. Moreover, alumina based catalysts, such as Al2O3 MgO/SiO2, exhibited high conversion and selectivity values (i.e., 99.0 and 97.0%, respectively) requiring regeneration over longer periods of operation [29].…”
Section: Ethylene (C2h4)mentioning
confidence: 93%
“…Currently, research work is mainly concentrated on the modification of HZSM-5, such as by ion exchange, hydrothermal treatment, and controlling surface acidic active sites and surface acid strength distribution, to improve the hydrothermal stability, anticoke ability, enhancing the activity and selectivity of HZSM-5. Recent studies have been reported by Zhang et al (2008) on the effect of the phosphorus content on the performance of phosphorus modified HZSM-5 catalysts in dehydration of ethanol to ethylene. They found that the main product was ethylene at 300-440 K and the anticoke ability of the catalysts modified by phosphorus of 3.4 w.t.% was improved, owing to the presence of weak acid sites after phosphorus modification.…”
Section: Catalysts For Microbial Ethanol Dehydrationmentioning
confidence: 99%